Homes under the microscope: results from a pilot community science approach to measure airborne microfibres in the home - Pringle, Kirsty J.; Sardo, Ana Margarida; Lamb-Riddell, Kathryn; De Vito, Laura; McGoran, Alexandra R.; Laggan, Sophie; Hansen, Mark; Cox, Timothy; Williams, Ben (Frontiers in Built Environment, 2025)
Non-natural airborne microfibres are an emerging concern in indoor air pollution, yet relatively little is known about their sources or concentrations. This is particularly relevant in home environments, where individuals spend significant amounts of time, but which are challenging for researchers to access at scale. Consequently, the concentration of indoor airborne microfibres remains poorly constrained. This paper presents results from the pilot phase of a participatory community (or citizen) science project, where participants collected airborne microfibres in their homes using simple, low-cost passive samplers consisting of Petri dishes lined with forensic tape. Microfibre deposition rates were then quantified through a combination of participant-contributed microscopy images and laboratory-based manual counting. The study found an average indoor microfibre deposition rate of 1,960 fibres m-2 day-1, with significant variability between homes (mean rates ranging from 570 to 4,534 fibres m-2 day-1). Among rooms sampled, bedrooms had the highest deposition rates (2,893 fibres m-2 day-1), followed by bathrooms (2,482 fibres m-2 day-1), with kitchens (1,225 fibres m-2 day-1) and living rooms (942 fibres m-2 day-1) showing lower rates. This study demonstrates a scalable, community-driven method for measuring indoor microfibres in the built environment.